Knowledge management model practices in business organisation : a theoretical model / Mohd Sazili Shahibi ... [et al.] - Shahibi, Mohd Sazili; Ibrahim, Zaharudin; Seman @ Kamarulzaman, Mohd Ridwan; Paiman, Mohd Jailani (Faculty of Information Management, 2005)
Knowledge Management is a process to manage and build organization strength and capabilities to compete in market. Its involved process like knowledge creation, knowledge captures knowledge dissemination and knowledge exploitation. Knowledge is also can be classified and modified that make it easier to re-use later as a corporate knowledge in an organization and keep them as an valuable asset in one system. The integration of corporate knowledge using knowledge management (KM) tools is important to the organization in order to cope with environmental changes both within and outside the organization, and to solve existing problem as well as to innovate for business expansion. The model is designed to capture and classified the knowledge, and then translate them into corporate knowledge. This is the major concern of this research. It also will be useful in determining the organization niche.